A stranding record of the short‐beaked common dolphin (Delphinus delphis) in Algerian West Coast, during 2008–2012. (23rd October 2019) - Larbi Doukara, Kamel
Abstract: Marine mammals stranding data provide valuable information on causes of mortality for cetacean populations. The aim of this study was to investigate the characteristics of the stranding events of common dolphins along the Algerian west coast, and estimate the proportion of human vs. non‐human induced mortality of the population. Between 2008 and 2012, out of the 52 cetacean stranding records along the Algerian west coast, common dolphins ( Delphinus delphis ) were recorded in 14 cases. All recorded strandings were of individual cases with no mass strandings registered during the reported period. To examine the proportion of human and non‐human induced mortality affecting this population, necropsies were conducted. In 10 cases, an interaction with some type of fishing gear had occurred; in three, there was no link with human activity; and in one case, it was not possible to determine the cause of death due to the condition of the carcass (severely decomposed).